Considerable international variation exists in blood pressure control and antihypertensive prescription patterns in chronic kidney disease - Alencar de Pinho, N; Levin, A; Jha, V (Elsevier, 2019)
Although blood pressure (BP) control is a major goal in chronic kidney disease (CKD), no worldwide overview of either its achievement or antihypertensive prescriptions is currently available. To evaluate this we compared crude prevalence of uncontrolled BP among 17 cohort studies, including 34 602 individuals with estimated glomerular filtration rate under 60 ml/min/1.73 m2 and treated hypertension across four continents, and estimated observed to expected prevalence ratios, adjusted for potential confounders. Crude prevalence of BP of 140/90 mm Hg or more varied from 28% to 61% and of BP of 130/80 or more from 54% to 84%. Adjusted prevalence ratios indicated poorer hypertension control than expected in cohorts from European countries, India, and Uruguay, and better control in patients from North American and high-income Asian countries. Four antihypertensive drug classes or more were prescribed to more than 30% of participants in North American and some European cohorts, but this practice was less common elsewhere. Renin angiotensin-aldosterone system (RAAS) inhibitors were the most common antihypertensive drugs, prescribed for 54% to 91% of cohort participants. Differences for other drug classes were much stronger, ranging from 11% to 79% for diuretics, 22% to 70% for beta-blockers, and 27% to 75% for calcium-channel blockers. The confounders studied explain only a part of the international variation in BP control among individuals with CKD. Thus, considerable heterogeneity in prescription patterns worldwide calls for further investigation into the impact of different approaches on patient outcomes.